THE EFFECT OF ATTITUDE, LEVEL OF EDUCATION AND SUPPORT OF HEALTH PERSONNEL ON THE ABILITY OF REGULATING DIET PATTERNS IN DIABETES MELLITUS PATIENTS USING A SELF-CARE THEORY APPROACH - Anggraeni, Dian; Fikriana, Riza; Nurbadriyah, Wiwit Dwi (PHARMACOLOGY, MEDICAL REPORTS, ORTHOPEDIC, AND ILLNESS DETAILS, 2022)
Diabetes mellitus is a chronic disease of metabolic disorders and hyperglycemia caused by impaired insulin secretion which is characterized by an increase in blood glucose levels exceeding normal limits (70-140 mg/dL). Diabetes mellitus can be caused by several factors, one of which is a poor diet. The purpose of this study was to analyze the effect of attitudes, education level and support of health workers on the ability to manage dietary patterns in diabetes mellitus sufferers using the Self-Care theory approach in Banjarejo Village, Pakis District. The research design used Analytical Observational with Cross-Sectional method. The sample used is 80 respondents using Non Probability Sampling with purposive sampling technique. The variables used are attitude, level of education, support of health workers and ability to manage diet patterns. The process of collecting data using a questionnaire in accordance with the inclusion and exclusion criteria, then data processing is carried out and followed by a statistical test of logistic regression using the help of a computer program. The results of the Logistic Regression Test showed that the variable that had the most influence on the ability to manage dietary patterns was the support of health workers variable with a significance value (p-value) of 0,044 < 0,05. As a result, it can be seen that health worker support is one of the factors that can affect a person's ability to manage diet patterns, and thus that there is a need for positive health worker support for diabetes mellitus patients in order to increase their ability to manage diet patterns and avoid uncontrolled increases in blood sugar levels or complications.